The pair ceramide 1-phosphate/ceramide kinase regulates intracellular calcium and progesterone-induced human sperm acrosomal exocytosis - Vaquer, Cintia C.; Suhaiman, Laila; Pavarotti, Martín A.; Arias, Rodolfo J.; Pacheco Guiñazú, Anahí B.; De Blas, Gerardo A.; Belmonte, Silvia A. (Frontiers in Cell and Developmental Biology, 2023)
Before fertilization, spermatozoa must undergo calcium-regulated acrosome exocytosis in response to physiological stimuli such as progesterone and zona pellucida. Our laboratory has elucidated the signaling cascades accomplished by different sphingolipids during human sperm acrosomal exocytosis. Recently, we established that ceramide increases intracellular calcium by activating various channels and stimulating the acrosome reaction. However, whether ceramide induces exocytosis on its own, activation of the ceramide kinase/ceramide 1-phosphate (CERK/C1P) pathway or both is still an unsolved issue. Here, we demonstrate that C1P addition induces exocytosis in intact, capacitated human sperm. Real-time imaging in single-cell and calcium measurements in sperm population showed that C1P needs extracellular calcium to induce [Ca2+]i increase. The sphingolipid triggered the cation influx through voltage-operated calcium (VOC) and store-operated calcium (SOC) channels. However, it requires calcium efflux from internal stores through inositol 3-phosphate receptors (IP3R) and ryanodine receptors (RyR) to achieve calcium rise and the acrosome reaction. We report the presence of the CERK in human spermatozoa, the enzyme that catalyzes C1P synthesis. Furthermore, CERK exhibited calcium-stimulated enzymatic activity during the acrosome reaction. Exocytosis assays using a CERK inhibitor demonstrated that ceramide induces acrosomal exocytosis, mainly due to C1P synthesis. Strikingly, progesterone required CERK activity to induce intracellular calcium increase and acrosome exocytosis. This is the first report, implicating the bioactive sphingolipid C1P in the physiological progesterone pathway leading to the sperm acrosome reaction.